Actinobacillus ureae: an unusual cause of tree-in-bud pattern in a case of pneumonia on lung computed tomographic scan—first clinical case report and review of the literature from India. (November 2016) - Dawar, R.; Nagarjuna, D.; Gupta, R.; Ghonge, N.P.; Sardana, R.
Abstract: A 62-year-old man with asthma sought care for intermittent fever, cough with expectoration, breathlessness and orthopnoea with grunting. Computed tomography revealed clusters of centrilobular nodules on both sides with a tree-in-bud appearance and mild diffuse bronchial wall thickening. Sputum sample grew pure colonies of Actinobacillus ureae which was confirmed by MALDI-TOF and 16SrRNA gene sequencing. A. ureae may be an additional bacteriologic causative agent of the tree-in-bud pattern on computed tomographic scan.